Effects of macroeconomic environment on non-performing loans and financial stability: Case of Bosnia and Herzegovina - Kemal Kozarić; Emina Žunić Dželihodžić (Journal of Central Banking Theory and Practice, 2020)
This paper analyses the impact of macroeconomic conditions on non-performing loans and financial stability in Bosnia and Herzegovina`s banking sector. The aim of this paper is to identify the effects of macroeconomic conditions on non-performing loans and the banking sector`s financial stability. To that end, data for the period 2006-2017 have been used. In order to detect the correlations between analysed variables, we performed the correlation analysis through Pearson coefficient of correlation. Results have confirmed the assumption about correlation between macroeconomic conditions, non-performing loans, and financial stability. Further, regression analysis was applied on data divided into two models: the impact of macroeconomic conditions on non-performing loans and the impact of macroeconomic conditions on the banking sector`s financial stability. Those two models point to the significance of macroeconomic environment for non-performing loans control and financial stability maintenance. Namely, the results have shown that improvement in macroeconomic conditions causes improvement in credit quality. Also, it was disclosed that better macroeconomic conditions ensure better conditions for maintenance of the banking sector`s financial stability.
Keywords: G00; G21; 330; Non-performing loans; Bank; Financial stability; Macroeconomic; Impact